Sidelobe Suppression Featuring the Phase Coherence Factor in 3-D Through-the-Wall Radar Imaging - N. S. N. Anwar; M. Z. Abdullah (Radioengineering, 2016)
Through-the-Wall Radar Imaging (TWRI) could be performed by beamforming of the signals from an array of ultrawideband (UWB) antennas. Preferably the imaging is done in 3-D so that both the position and the height of the target be revealed. This is possible with planar array antenna geometry. However, implementing this technique that fulfills Nyquist criterion leads to a large number of antennas while sparse array suffers from an increase of the sidelobe level. In this work, the Phased Coherence Factor (PCF) is applied to conventional delay and sum (DAS) beamformer to suppress the sidelobe of a sparse planar antenna array. The performance of the proposed technique is experimentally evaluated in terms of the target-to-clutter ratio (TCR), and the separation resolution. It is discovered that PCF is effective in reducing the sidelobe’s artifacts, resulting in TCR of greater than 20 dB and a separation resolution of 20 cm at 2.5 m range.